Avian Influenza: A Comprehensive Systematic Review Of Epidemiology, Clinical Manifestations, Diagnostic Approaches, Prevention Strategies, Recent Outbreaks and Global Collaboration - Sakshi Patel; Poorvi; Yash Raj Gupta; Ayush Pandey; Elby K Paul; Kuldeep Singh; Rajdeep Paul (Revista Electronica de Veterinaria, 1970)
Avian influenza (AI) viruses, including highly pathogenic subtypes such as H5N1, H7N9, and H9N2, pose significant threats to global public health and agriculture. This systematic review synthesizes current knowledge on AI, encompassing epidemiology, clinical manifestations, diagnostic methods, prevention strategies, recent outbreaks, specific challenges in India, and global collaboration efforts. The review underscores the critical role of international cooperation in mitigating AI's impact on health security and economic stability.